Diagnostic value of cardiac marker concentrations in patients with heart failure depending on frailty syndrome - V. A. Safronenko; A. I. Chesnikova; V. L. Korobka (Российский кардиологический журнал, 2024)
Aim. To evaluate the diagnostic value of the serum level of N-terminal pro-brain natriuretic peptide (NT-proBNP), soluble growth stimulation expressed gene 2 (sST2) and galectin-3 to detect heart failure (HF) in patients with hypertension (HTN) aged 80 years and older depending on frailty syndrome (FS).Material and methods. A total of 320 patients with HTN depending on the presence of HF and FS were divided into following groups: group 1A — patients with HTN, FS and HF (n=84), group 1B — patients with HTN, FS without HF (n=77), group 2A — patients with HTN, HF without FS (n=84), group 2B — patients with HTN without HF and without FS (n=75). FS was identified using the Age Is No Disqualification questionnaire. The serum levels of NT-proBNP, sST2 and galectin-3 were determined by the enzyme immunoassay. ROC analysis was used to determine the threshold value of the markers.Results. In patients of group 2B, NT-proBNP concentrations were below the threshold level (<125 pg/ml), while the sST2 level was within the average normal values; the galectin-3 concentration was increased. In group 1B, elevated levels of NT-proBNP (244,5 pg/ml) and galectin-3 (16,1 ng/ml) were observed. The highest values of all three markers were recorded in patients of group 1A in comparison with both patients of group 1B and patients of group 2A. To diagnose heart failure in patients with HTN without FS aged 80 years and older, the threshold level of galectin-3 was determined (15,9 ng/ml, p<0,001). In patients with HTN and FS, the threshold level of NT-proBNP (365,9 pg/ml, p<0,001) and galectin-3 (30 ng/ml, p<0,001) was calculated.Conclusion. For the diagnosis of HF in patients with HTN aged 80 years and older without FS, the most informative markers are NT-proBNP and sST2 (the level did not depend on age); in patients with HTN aged 80 years and older with FS — sST2 (the level did not depend on either age or FS). New threshold levels of NT-proBNP and galectin-3 were determined to confirm HF in patients with HTN and FS.